2016
DOI: 10.1128/jb.00490-16
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone Isomerase from Eubacterium ramulus Catalyzes the Ring Contraction of Flavanonols

Abstract: The enzyme catalyzing the ring-contracting conversion of the flavanonol taxifolin to the auronol alphitonin in the course of flavonoid degradation by the human intestinal anaerobe Eubacterium ramulus was purified and characterized. It stereospecifically catalyzed the isomerization of (؉)-taxifolin but not that of (؊)-taxifolin. The K m for (؉)-taxifolin was 6.4 ؎ 0.8 M, and the V max was 108 ؎ 4 mol min ؊1 (mg protein) ؊1 . The enzyme also isomerized (؉)-dihydrokaempferol, another flavanonol, to maesopsin. Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…Based on a thorough literature review, some of our results and observations are completely new findings, while several other findings can be supported by previous reports in the literature. For example, previous studies have revealed that Eubacterium in phyla Firmicutes is generally considered a health-promoting gut microbe 41,42 , and this bacterial genus was detected at relatively decreased abundance in the S-Str compared to other groups, which echos the fact that stress generates adverse health effects to the gut microbes. It is also interesting to note that the www.nature.com/scientificreports www.nature.com/scientificreports/ lactate level of rats' cecum samples significantly elevated immediately after the stress event in this study, which could contribute to gut dysbiosis and increased host gut permeability and inflammation 43 .…”
Section: Resultsmentioning
confidence: 91%
“…Based on a thorough literature review, some of our results and observations are completely new findings, while several other findings can be supported by previous reports in the literature. For example, previous studies have revealed that Eubacterium in phyla Firmicutes is generally considered a health-promoting gut microbe 41,42 , and this bacterial genus was detected at relatively decreased abundance in the S-Str compared to other groups, which echos the fact that stress generates adverse health effects to the gut microbes. It is also interesting to note that the www.nature.com/scientificreports www.nature.com/scientificreports/ lactate level of rats' cecum samples significantly elevated immediately after the stress event in this study, which could contribute to gut dysbiosis and increased host gut permeability and inflammation 43 .…”
Section: Resultsmentioning
confidence: 91%
“…By combining ERED with CHI, Gall et al observed the conversion of naringenin to phloretin; coexpression of ERED and CHI led to transformation of eriodictyol and homoeriodictyol in addition to naringenin (12). Based on this report, we intended to use ERED as an auxiliary enzyme in order to compare the rate of taxifolin conversion by CHI (14) to that of naringenin conversion. Unexpectedly, it turned out that phloretin formation from naringenin depended on ERED but not CHI concentration and occurred even in the absence of CHI.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of flavanonols by enzymes from E. ramulus depends on the stereoisomeric form and the availability of NADH. While (2R,3R)-stereoisomers are isomerized by CHI to the corresponding auronols (14), Fcr NADH-dependently forms hydroxydihydrochalcones from (2S,3S)-flavanonols. However, the naturally occurring flavanonols exist in their (2R,3R)form, which at least has been demonstrated for taxifolin (23,41,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecule can be metabolized by gut microbiota to render 8-prenylnaringenin [72,73] through an O-demethylation that is carried out by Eubacterium species and particularly by Eubacterium limosum or Eubacterium ramulus that is responsible for this transformation [75]. The genus Eubacterium is one of the biggest butyric acid producers [87] and deserves further investigation. However, little attention has been paid to other hops compounds such as alpha- and beta-acids and their interaction with gut microbiota.…”
Section: Beer Polyphenols and Its Relationship With Gut Microbiotamentioning
confidence: 99%